ASPEK HUKUM PENGGUNAAN TANDA TANGAN DIGITAL DALAM TRANSAKSI BISNIS - Mulyana, Yusep (VARIA HUKUM, 2021)
The legal power of digital signatures in business transactions is the Law of the Republic of Indonesia Number 11 of 2008 concerning Electronic Information and Transactions, which explicitly acknowledges that electronic signatures have legal force and legal consequences as long as the electronic signature follows the requirements stated in Article 11 of the ITE Law which is a minimum requirement and must be met in every electronic signature creation, the level of security of an electronic signature will be guaranteed if it has an electronic certificate containing the information or identity of the user, the electronic certificate is obtained on the basis of an application to the Certification Authority (CA) by the user (subscriber) . Dispute Resolution in the Use of Digital Signatures in business transactions is based on the agreement of both parties regarding the choice of law and the institution that resolves the problems that occur. Â